Mate Preference Necessities in Long- and Short-Term Mating: People Prioritize in Themselves What Their Mates Prioritize in Them - LI, Norman P. (Institutional Knowledge at Singapore Management University, 2007)
People were given highly constrained low budgets of mate dollars to allocate across various characteristics pertaining to their ideal partners and to their ideal selves for long- and short-term mating. First, results replicated findings from LI et al. (2002) and LI and KENRICK (2006). For ideal long-term mates, men prioritized physical attractiveness and women prioritized social status. For ideal short-term mates, both sexes prioritized physical attractiveness. Second, people's design of their ideal selves mirrored what the opposite sex ideally desired in their mates. For a long-term mating context, men prioritized social status in themselves and women prioritized physical attractiveness in themselves. For ideal short-term selves, both sexes prioritized physical attractiveness. Findings were consistent with a domain-specific view of psychological mechanisms, in that processes for valuing potential mates and processes for valuing one's own mate value may be specialized mechanisms.